The Importance of Equity Finance for R&D Activity - Are There Differences Between Young and Old Companies? - Elisabeth Müller; Volker Zimmermann (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2006)
This paper analyzes the importance of equity finance for the R&D activity of small and medium-sized enterprises. We use information on almost 6000 German SMEs from a company survey. Using the intensity of banking competition at the district level as instrument to control for endogeneity, we find that a higher equity ratio is conducive to more R&D for young but not for old companies. Equity may be a constraining factor for young companies which have to rely on the original equity investment of their owners since they have not yet accumulated retained earnings and can relay less on outside financing. The positive influence is found for R&D intensity but not for the decision whether to perform R&D. Equity financing is therefore especially important for the most innovative, young companies.
urn:nbn:de:bvb:19-epub-13440-3
Keywords: G32; O32; 330; R&D activity; equity finance; small and medium-sized enterprises